Challenges and opportunities of complexity theory in health care systems - Ashraf A'aqoulah, PhD; Ashraf A. El-Metwally, PhD; Bader Al Khateeb, PhD; Duaa Alammari, PhD; Awad Alshahrani, PhD; Aljohara Aldubikhi, PhD; Abdulrahman Alsulami, Ms.c; Faris Fatani, MD; Nisreen Innab, PhD (Journal of Taibah University Medical Sciences, 2025)
الملخص: اقترحت الدراسات المنشورة مؤخرًا حول الصحة والتعقيد تعريفًا جديدًا للصحة يشمل الطبيعة المنهجية للصحة لتصوير التعقيد الكامن في الصحة. يوضح التفاعل بين الطبيب والمريض العديد من خصائص النظام التكيفي المعقد. تعكس الطبيعة المعقدة لنظام الرعاية الصحية الأولية، وتعقيد تحليلات البيانات في الوقت الفعلي في الرعاية الصحية باستخدام أنظمة المعلومات، والتعقيد المحيط بوصف الأدوية المزيد من التعقيد في نظام الرعاية الصحية. تتطلب هذه الجوانب تحويل الرعاية الصحية من نظام يركز على الخدمة إلى نظام يركز على البيئة، باستخدام نموذج بحثي معقد للمعرفة الإلكترونية للشبكة يوفر مشاركة المجتمع في صنع القرار لتحسين الصحة وينطوي على قيادة تكيفية تنفذ استراتيجيات مختلفة لحل المشاكل المعقدة. في الواقع، من الضروري استخدام نهج متعدد التخصصات لإعادة تصميم النظام الصحي من خلال تطوير أنظمة مراقبة وتقييم فعالة داخل الأنظمة الصحية، وسلامة المرضى، وشفافية المعلومات، والاستخدام الفعال لتكنولوجيا المعلومات لتحسين جودة الخدمات المقدمة. Abstract: Recent studies of health and complexity have proposed a new definition of health that encompasses the systematic nature of health in order to depict its inherent complexity. The interaction between a clinician and patient has many of the characteristics of a complex adaptive system. The complex nature of primary health care systems, the complexity of real-time data analytics in health care using information systems, and complexity related to the prescription of drugs further reflect the complexity of health care systems. These characteristics indicate that it is necessary to transform health care from an egocentric system to an ecocentric system by using a complex network electronic knowledge research model that provides community engagement in decision making for health improvement and involves adaptive leadership implementing different strategies for solving complex problems. Indeed, it is essential to use a transdisciplinary approach to redesign the health system by developing effective monitoring and evaluation systems inside health systems to ensure patient safety and information transparency, and the effective use of information technology to improve the quality of the services delivered.